Multicultural Communication in the Character Development of Santri at Pesantren Tebuireng - Dimas Setyawan Saputro; Faizatul Mukarromah; Al Hidayahtul Mus Qoimah; Luluk Fikri Zuhriyah (Mediakita, 2025)
The issue of multiculturalism in Indonesia is a topic that is often discussed. The thing that drives the conversation departs from the many cases related to social and cultural differences that are not recognized and respected amid community life. This research aims to provide an overview of multicultural values through communication so that they can be appropriately conveyed to the students of Pesantren Tebuireng. The method used in this research is qualitative with a case study approach. The results of this study indicate that multicultural communication by Pesantren Tebuireng is carried out in several ways, including holding national workshops, filming national figures, bandongan recitation, designing santri study rooms, and queuing culture. This gives the santri's character a spirit of nationalism and love for the country. In addition, it also encourages santri to apply the values of Pancasila to everyday life.